Marketing Strategy: Segmenting, Targeting, and Positioning for Digital Business (Literature Review) - Rio Luthfiandana; Gratia Atanka Barus; Nuraeni Nuraeni; Sri Yanthy; Herni Pujiati (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
The marketing strategy article: segmenting, targeting and positioning for digital business is a scientific literature review article within the scope of marketing management science. The purpose of writing this literature article is to create a hypothesis regarding the relationship between factors, which can then be used for further research in the field of human resource management. Descriptive qualitative research methods were applied in this research. The data used in this research comes from previous research which is still relevant to the current investigation. Data was obtained from credible academic online platforms, including Publish or Perish, Google Scholar, digital reference books, and reputable journals. The findings of this research are as follows: 1) Segmenting influences marketing strategies for digital businesses; 2) Targeting influences marketing strategies for digital businesses; and 3) Positioning influences marketing strategies for digital businesses.